Soggetti emergenti - Redazione, La camera blu (La camera blu. Rivista di studi di genere, 2014)
With this issue La camera blu moves to the web, to SERENA, the platform created by the University of Naples Federico II for its on line journals. Though this choice has been ultimately unavoidable – as it is becoming more and more difficult to obtain the small amount of funding necessary for the paper edition – we believe that this new ver-sion will provide opportunities for enriching the quality of the journal and extend the sphere of its relationships.